Comparison of Optomap ultrawide-field imaging versus slit-lamp biomicroscopy for assessment of diabetic retinopathy in a real-life clinic - Purbrick RMJ (Dove Medical Press, 2014)
Robert M J Purbrick, Shahrnaz Izadi, Ankur Gupta, N Victor Chong Oxford Eye Hospital, John Radcliffe Hospital, Oxford, UK Purpose: We aimed to assess the agreement between clinical assessment of diabetic retinopathy and Optomap ultrawide-field imaging (UWFI) in a real-life clinic setting. Methods: Structured examination findings, from diabetic patients attending routine medical retina clinics in July 2011, were retrospectively compared with the grade obtained from Optomap UWFI images, graded independently by two ophthalmologists, taken at the same visit. Results: A total of 84 eyes (42 patients) were examined, and 74 eyes (37 patients) were suitable for analysis. The hospital Eye Service slit-lamp biomicroscopy grades for retinopathy were: no diabetic retinopathy in zero eyes; background retinopathy in 21 eyes; preproliferative retinopathy in 34 eyes; and proliferative retinopathy in 19 eyes. For retinopathy, the agreement between the Optomap UWFI and clinical grading was moderate for both graders (κ=0.57 and κ=0.63), and there was almost perfect agreement between the two graders (κ=0.92). The clinical grades for the presence of photocoagulation scars were: no photocoagulation scars in 46 eyes and photocoagulation scars visible in 28 eyes, indicating substantial agreement between the Optomap UWFI and clinical grading for both graders (κ=0.73 and κ=0.64). There were two instances where proliferative retinopathy was documented clinically but graded as preproliferative by both graders of Optomap UWFI. These were investigated, and neither patient required treatment, ie, the difference in retinopathy grade would not have affected the patient outcomes. Conclusion: This study demonstrated moderate agreement between Optomap UWFI and hospital slit-lamp biomicroscopy grading of patients’ retinopathy in a real-life medical retina clinic setting. The authors believe that Optomap UWFI is, not only a very useful adjunct to clinical examination in terms of detection and recording of retinopathy, but also, could have a role in standalone “virtual” clinics. Keywords: photography